2007
DOI: 10.1007/s00213-007-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

A stimulus-control account of regulated drug intake in rats

Abstract: Rationale-Patterns of drug self-administration are often highly regular, with a consistent pause following each self-injection. This pausing might occur because the animal has learned that additional injections are not reinforcing once the drug effect has reached a certain level, possibly due to the reinforcement system reaching full capacity. Thus, interoceptive effects of the drug might function as a discriminative stimulus, signaling when additional drug will be reinforcing and when it will not.Objective-To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 30 publications
6
29
0
Order By: Relevance
“…That is, under conditions with no time-out following a reinforcer delivery, the animals could make two responses in quick succession (resulting in delivery of a larger total unit dose); however, the typical finding is that the distribution of inter-response intervals simply shifts to the left (i.e., smaller intervals). Regardless of the reason this happens (see Panlilio et al 2007 for a stimulus control account of this phenomenon, and below for reference to other accounts), responding under the present schedule conditions seems to represent an extreme example of this phenomenon. Animals respond with a relatively short hold-down duration (followed by a relatively small reinforcer), and the inter-response interval gets shorter in a proportionately appropriate manner.…”
Section: Discussionmentioning
confidence: 72%
“…That is, under conditions with no time-out following a reinforcer delivery, the animals could make two responses in quick succession (resulting in delivery of a larger total unit dose); however, the typical finding is that the distribution of inter-response intervals simply shifts to the left (i.e., smaller intervals). Regardless of the reason this happens (see Panlilio et al 2007 for a stimulus control account of this phenomenon, and below for reference to other accounts), responding under the present schedule conditions seems to represent an extreme example of this phenomenon. Animals respond with a relatively short hold-down duration (followed by a relatively small reinforcer), and the inter-response interval gets shorter in a proportionately appropriate manner.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies showed increased subjective, behavioral, physiological, and neuronal responses to smoking cues when smoking seems available (Carter and Tiffany, 2001;Wertz and Sayette, 2001;Wilson et al, 2004;McBride et al, 2006). Other studies showed that the end of drug consumption and stimuli predicting the nonoccurrence of the drug reduce drug seeking and wanting (Kearns et al, 2005; see also Panlilio et al, 2008). In sum, these results point to an inhibitory nature of END-stimuli.…”
Section: Introductionmentioning
confidence: 78%
“…Importantly, one should not prematurely assume ENDsmoking-stimuli to be simply weak cues because Mucha et al (2008) demonstrated that these stimuli are able to reduce the effects of BEGIN-smoking-stimuli when both are presented together. Similarly, other studies suggest that the end of drug consumption and stimuli predicting the nonoccurrence of the drug may reduce drug seeking and wanting (Kearns et al 2005; see also Panlilio et al 2008). Thus, END-smoking-stimuli seem to trigger a unique reactivity, which may even oppose responses triggered by BEGINsmoking-stimuli (Mucha et al 2008;Stippekohl et al 2010).…”
Section: Introductionmentioning
confidence: 95%